Easy Japanese phrase book : over 1500 common phrases for everyday use and travel. (Lingo Mastery, 2023)
Most textbooks are made to teach you the traditional rules and structures of a language and are great for getting around the grammar and spelling questions you may have. However, how many of them provide you the tools necessary to have a common conversation with a best friend or someone you've just met? Not many at all. Language learners often complain about this - a lack of material that can help you familiarize yourself with the most common phrases used in everyday conversation and in native surroundings.